2012
DOI: 10.1590/s0036-46652012000100001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and antifungal susceptibility testing of Trichosporon asahii in Ceará, Brazil

Abstract: SUMMARYTrichosporon spp. are yeasts capable of causing invasive disease, which mainly affect immunocompromised patients. A clinical strain of T. asahii was isolated from the blood cultures of patients admitted to the General Hospital of Fortaleza. Susceptibility tests were conducted by disk diffusion and broth microdilution. The isolated strain of T. asahii was resistant to fluconazole. The patient used amphotericin B and caspofungin in order to facilitate the microbiological cure. It was the first isolation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
6
0
3
Order By: Relevance
“…Basetti et al firstly used liposomal AmB and caspofungin to successfully treat an acute leukemia patient with T. asahii fungaemia [3]. De Vasconcelos and his colleagues cured an invasive T. asahii infection in an acute myeloid patient by AmB with caspofungin [14]. Our observation suggested that even with a lower dose, the combination therapy of liposomal AmB and caspofungin may synergistically improve the antifungal activity with better tolerance.…”
Section: Discussionmentioning
confidence: 62%
“…Basetti et al firstly used liposomal AmB and caspofungin to successfully treat an acute leukemia patient with T. asahii fungaemia [3]. De Vasconcelos and his colleagues cured an invasive T. asahii infection in an acute myeloid patient by AmB with caspofungin [14]. Our observation suggested that even with a lower dose, the combination therapy of liposomal AmB and caspofungin may synergistically improve the antifungal activity with better tolerance.…”
Section: Discussionmentioning
confidence: 62%
“…For comparison analysis, the cases were clustered according to the main underlying disease, e.g., homeopathy ( n = 79; Grauer et al, 1994 ; Higgins et al, 1994 ; Hsiao et al, 1994 ; Nasu et al, 1994 ; Hung et al, 1995 ; Spánik et al, 1995 ; Itoh et al, 1996 ; Fanci et al, 1997 ; Kataoka-Nishimura et al, 1998 ; Sklair-Levy et al, 1998 ; Krcmery et al, 1999 ; Takamura et al, 1999 ; Erer et al, 2000 ; Kim et al, 2001 ; Moretti-Branchini et al, 2001 ; Fournier et al, 2002 ; Hadley et al, 2002 ; Meyer et al, 2002 ; Chang et al, 2003 ; Marty et al, 2003 ; Bassetti et al, 2004 ; Chowdhary et al, 2004 ; Viscomi et al, 2004 ; Antachopoulos et al, 2005 ; Chan-Tack, 2005 ; Akagi et al, 2006 ; Ghiasian et al, 2006 ; Kendirli et al, 2006 ; Koyanagi et al, 2006 ; Matsue et al, 2006 ; Meguro-Hashimoto et al, 2006 ; Rodrigues et al, 2006 ; Hara et al, 2007 ; Miura et al, 2007 ; Rieger et al, 2007 ; Bayramoglu et al, 2008 ; Hosoki et al, 2008 ; Thibeault et al, 2008 ; Tsuji et al, 2008 ; Fekkar et al, 2009 ; Walia et al, 2009 ; Gabriel et al, 2011 ; Kudo et al, 2011 ; Hosokawa et al, 2012 ; Menezes et al, 2012 ; Chen et al, 2014 ; Issarachaikul et al, 2014 ; Karapinar et al, 2014 ; Capoor et al, 2015 ; Odero et al, 2015 ; Pérard et al, 2015 ; Tanyildiz et al, 2015 ), other immunodeficiency conditions ( n = 41; Canales et al, 1998 ; Lascaux et al, 1998 ; Anuradha et al, 2000 ; Piwoz et al,…”
Section: Resultsunclassified
“…Essa transição ainda não é bem compreendida, mas estudos apontam que a capacidade desse microrganismo em produzir fatores de virulência aliada ao sistema imune do hospedeiro não plenamente funcionante podem ser os fatores que auxiliam na instalação da condição patológica. (15,16) Figura 2. Halo de inibição formado pelo fluconazol e anfotericina B frente a C. albicans, pelo método de disco-difusão em meio MHA suplementado com glicose 2% e 0,5 μg/mL de azul de metileno.…”
Section: Discussionunclassified
“…(11,12) Após a leitura e mensuração dos halos, em milíme-tros, os resultados foram comparados com a tabela fornecida pelo fabricante (Cecon). Para anfotericina B, halo > 10 mm (Sensível) e <10 mm (Resistente); nistatina, halo >10 mm (Sensível) e ≤10 mm (Resistente); cetoconazol, halo > 20 mm (Sensível), halo [10][11][12][13][14][15][16][17][18][19][20] Valor dos halos medidos em milímetro (mm). C-contaminação.…”
Section: Preparação Dos Meiosunclassified